HUBUNGAN PEMBERIAN ASI EKSLUSIF DENGAN KEJADIAN STUNTING PADA BALITA 6 BULAN SAMPAI 1 TAHUN DI PUSKEMAS LELES GARUT - Anita Putri Wijayanti; Neng Indri Indriani; Sri Hayati (LPPM Universitas Adhirajasa Reswara Sanjaya, 2025)
Stunting in childhood is the best indicator of child welfare and is an accurate reflection of social inequality. The causes of stunting are caused by multiple dimensions, including providing nutrition to toddlers, the highest toddler nutrition is found in breast milk. Stunting is only visible when the child reaches the age of 6 months to 1 year. This study is to analyze the Relationship between Exclusive Breastfeeding and the Incidence of Stunting in Toddlers aged 6 months to 1 year at the Leles Garut Community Health Center. The type of research used in this study is quantitative research using a correlational study research design. The population in this study were all mothers who had toddlers aged 6 months to 1 year who were not diagnosed with disease in the working area of the Leles Garut Community Health Center, totaling 424. The sampling technique in this study used accidental sampling, namely the sample taken was all mothers who had toddlers and came to the integrated health post during the 2 weeks of the study, obtained 98 respondents. The research will be conducted on August 7 – August 21, 2024. The instruments in the study used questionnaires, microtoice and Z-Score tables. The data analysis technique used for univariate data used percentages and bivariate data used Chi-Square. Results: Most toddlers were not given Exclusive Breastfeeding and stunting occurred, namely 53 respondents (54.1%). Most (54.1%) or 53 respondents were not given Exclusive Breastfeeding, namely. There is a significant relationship between the two variables, namely with a value (p-value = 0.000), with a very strong level of relationship. Suggestions To increase the role of health workers to improve counseling and provide information about Exclusive Breastfeeding. Conclusion: Stunting can occur if children are not given Exclusive Breastfeeding according to their age.